Unifikasi Qira’at Dan Standarisasi Bacaan Al-Qur’an: Analisis Terhadap Peran Ilmu Qira’at Dalam Menjaga Integritas Teks: Unification of Qira'at and the Standardization of Qur'anic Recitation: An Analysis of Qira'at Science's Role in Preserving Textual Integrity - Muhammad Sirril Wafa; Muhammad Habib Rizieq Hidayat; Ahmad Saerozi (Ulumul Qur'an: Jurnal Kajian Ilmu Al-Qur'an dan Tafsir, 2026)
This study aims to explain the relationship between the plurality of qiraat and the process of Quranic standardization in the modern era, in which the Hafs an Asim narration accounts for approximately 95% of global mushaf circulation. Using a qualitative, descriptive-analytical approach, this research examines classical and modern scholarly literature. The novelty of this study lies in the clear distinction between unification as a theological belief in all valid recitations and standardization as a practical-pedagogical necessity. The findings indicate that the global dominance of the Hafs narration resulted from systematic educational standardization and mass-printing policies, beginning in 1924 with the Cairo Mushaf and in 1985 with the King Fahd Complex, rather than from the invalidity of other narrations. The contribution of this research is providing an integrative model that positions the science of qiraat as an epistemic control system that balances linguistic diversity with the social need for a single standard. These findings are crucial for correcting public perception and maintaining deep respect for the various valid and mutawatir narrations within the Islamic intellectual tradition.